Two-sided markets: the case for (Or Against) a free sports newspaper in Portugal - Morgado, Maria Beatriz das Neves (2018)
Could a free sports newspaper be successful in Portugal? We answer this question by (i) extensively analyzing the literature addressing the evolution of the newspaper industry—currently undergoing significant change and concomitantly facing financial turmoil, (ii) interviewing several key agents in the industry and (iii) conducting a survey of potential readers. We conclude that a free sports newspaper would not be economically successful in Portugal at this juncture.